tRNA gene content, structure, and organization in the flowering plant lineage - Monloy, Kim Carlo; Planta, Jose (Frontiers in Plant Science, 2024)
Transfer RNAs (tRNAs) are noncoding RNAs involved in protein biosynthesis and have noncanonical roles in cellular metabolism, such as RNA silencing and the generation of transposable elements. Extensive tRNA gene duplications, modifications to mature tRNAs, and complex secondary and tertiary structures impede tRNA sequencing. As such, a comparative genomic analysis of complete tRNA sets is an alternative to understanding the evolutionary processes that gave rise to the extant tRNA sets. Although the tRNA gene (tDNA) structure and distribution in prokaryotes and eukaryotes, specifically in vertebrates, yeasts, and flies, are well understood, there is little information regarding plants. A detailed and comprehensive analysis and annotation of tDNAs from the genomes of 44 eudicots, 20 monocots, and five other non-eudicot and non-monocot species belonging to the Ceratophyllaceae and the ANA (Amborellales, Nymphaeales, and Austrobaileyales) clade will provide a global picture of plant tDNA structure and organization. Plant genomes exhibit varying numbers of nuclear tDNAs, with only the monocots showing a strong correlation between nuclear tDNA numbers and genome sizes. In contrast, organellar tDNA numbers varied little among the different lineages. A high degree of tDNA duplication in eudicots was detected, whereby most eudicot nuclear genomes (91%) and only a modest percentage of monocot (65%) and ANA nuclear genomes (25%) contained at least one tDNA cluster. Clusters of tRNATyr–tRNASer and tRNAIle genes were found in eudicot and monocot genomes, respectively, while both eudicot and monocot genomes showed clusters of tRNAPro genes. All plant genomes had intron-containing tRNAeMet and tRNATyr genes with modest sequence conservation and a strictly conserved tRNAAla-AGC species. Regulatory elements found upstream (TATA-box and CAA motifs) and downstream (poly(T) signals) of the tDNAs were present in only a fraction of the detected tDNAs. A and B boxes within the tDNA coding region show varying consensus sequences depending on the tRNA isotype and lineage. The chloroplast genomes, but not the mitogenomes, possess relatively conserved tRNA gene organization. These findings reveal differences and patterns acquired by plant genomes throughout evolution and can serve as a foundation for further studies on plant tRNA gene function and regulation.